2021
DOI: 10.1186/s13012-021-01151-x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effects of the INFORM cluster randomized trial: an observational post-intervention study

Abstract: Background Numerous studies have examined the efficacy and effectiveness of health services interventions. However, much less research is available on the sustainability of study outcomes. The purpose of this study was to assess the lasting benefits of INFORM (Improving Nursing Home Care Through Feedback On perfoRMance data) and associated factors 2.5 years after removal of study supports. INFORM was a complex, theory-based, three-arm, parallel cluster-randomized trial. In 2015–2016, we success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…We found that care aides’ engagement in formal interactions was negatively associated with the meaning derived from their work. An earlier clinical trial, Improving Nursing Home Care Through Feedback on Performance Data (INFORM), within the TREC program demonstrated that including care aides in resident care decisions (formal interactions) was only successful when a supportive work culture was present ( Hoben et al, 2021 ). Involving care aides in formal communication and decision making about residents must be initiated by the managerial team and encouraged with appropriate information and feedback mechanisms ( Hoben et al, 2020 ), as it can lead to low turnover, higher retention rates, higher aggregate social engagement scores, and lower incidence of pressure ulcers for residents in nursing homes ( Barry et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that care aides’ engagement in formal interactions was negatively associated with the meaning derived from their work. An earlier clinical trial, Improving Nursing Home Care Through Feedback on Performance Data (INFORM), within the TREC program demonstrated that including care aides in resident care decisions (formal interactions) was only successful when a supportive work culture was present ( Hoben et al, 2021 ). Involving care aides in formal communication and decision making about residents must be initiated by the managerial team and encouraged with appropriate information and feedback mechanisms ( Hoben et al, 2020 ), as it can lead to low turnover, higher retention rates, higher aggregate social engagement scores, and lower incidence of pressure ulcers for residents in nursing homes ( Barry et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurse empowerment and leadership were identified as likely elements for a better management of acute changes in NHRs’ conditions [ 21 ]. Hoben and colleagues [ 36 ] confirmed the effectiveness and sustainability [ 37 ] of nursing staff’s involvement in improving the interprofessional exchange about NHRs’ health. Change agents in all three trials were trained, received implementation material and were supervised regularly.…”
Section: Discussionmentioning
confidence: 99%
“…Using descriptive statistics, baseline characteristics of LTC homes, care units, care aides, and residents were compared between study arms. To assess intervention effectiveness, mixed effects regression models were used [ 99 , 100 ]. All models were adjusted for sampling strata, baseline differences of the outcome variables, care aide characteristics (sex, age, English as first language [yes/no]), and care unit staffing (total care hours per resident day and percentage of total hours per resident day provided by care aides).…”
Section: Methodsmentioning
confidence: 99%